AN ATTEMPT TO DEVELOP MULTIPLE INTELLIGENCE-BASED TEACHING MATERIALS: NEED ANALYSIS AND RECOMMENDATIONS - Agrissto Bintang Aji Pradana; Umi Rachmawati; Nidya Anscalia Azka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Teaching material is important to be applied in the teaching and learning process. It is supposed to be related to the student’s needs and traits. Nevertheless, there are several appropriateness of worksheet compiling as supporting material. The research in this paper attempted to find out the need for Multiple Intelligence-based student’s worksheet developments and offer possible recommendations. It employed a qualitative approach and involved 13 English teachers as respondents. They were from selected elementary schools located in various regencies in Central Java. A set of questionnaires was administered and delivered online through Google Forms. It is provided a number of closed and open-ended questions related to the existing curriculum, competency, media and activities, students’ characters, and challenges in compiling the student’s worksheet. The data were analyzed qualitatively. The results reveal that there was a lack of compulsory curriculum and competency, appropriate activities, and environmental interactions. Thus, it is recommended for teachers to take a well-planned curriculum; various activities connected to parental supports, realia, digital tools; and students’ personal traits in developing students’ worksheets. It is a reference to promote a better quality of Teaching English to Young Learners.